2014
DOI: 10.1113/expphysiol.2014.083394
|View full text |Cite
|
Sign up to set email alerts
|

The claudin‐16 channel gene is transcriptionally inhibited by 1,25‐dihydroxyvitamin D

Abstract: New Findings r What is the central question of this study?In the kidney, the bulk of the filtered Mg 2+ is reabsorbed in the thick ascending limb by paracellular conductance, mediated by the tight junction protein, claudin-16, which is encoded by the gene CLDN16.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…) and claudin‐16 (Kladnitsky et al. ); however, not all studies show this negative regulation (reviewed by Zhang et al. ), suggesting that the effects of 1,25(OH) 2 D might be context or site dependent and reflect the complex nature of the tight junction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…) and claudin‐16 (Kladnitsky et al. ); however, not all studies show this negative regulation (reviewed by Zhang et al. ), suggesting that the effects of 1,25(OH) 2 D might be context or site dependent and reflect the complex nature of the tight junction.…”
Section: Discussionmentioning
confidence: 99%
“…For example, claudin-2 protein was inhibited by in vitro treatment of duodenal cells with 1,25(OH) 2 D (Du et al 2015). Other claudins can be negatively regulated by 1,25(OH) 2 D, including claudin-5 (Won et al 2015) and claudin-16 (Kladnitsky et al 2015); however, not all studies show this negative regulation (reviewed by Zhang et al 2013), suggesting that the effects of 1,25(OH) 2 D might be context or site dependent and reflect the complex nature of the tight junction. Future studies may also choose to validate the reduced claudin-1 protein levels we observed (using immunofluorescence) by other means (e.g., western blot), and measure the effects of vitamin D supplementation on the expression of other claudins and proteins associated with the tight junction.…”
Section: Discussionmentioning
confidence: 99%
“…2013) and Mg 2+ (claudin‐16: Kladnitsky et al . 2015). Recently, the increase in intestinal absorption of P i (and Ca 2+ ) induced by lithocholic acid was reported to require the Vdr but to be independent of NaPi‐IIb (Hashimoto et al .…”
Section: Introductionmentioning
confidence: 99%
“…Hypomagnesaemia in mice increases both claudin-16 protein and mRNA abundance, while Mg 2+ -loaded animals down-regulated claudin-16 ( 153 ) . The expression of claudin-16 is inhibited by calcitriol ( 154 ) and further influenced by a variety of hormones such as glucagon, insulin, calcitonin, vasopressin or isoproterenol ( 155 ) , which makes it difficult to evaluate these effects in vivo . Furthermore, Ca 2+ transport via claudin-16 is reduced by Mg 2+ ( 156 ) : ‘A competitive transport of Mg 2+ and Ca 2+ via the common paracellular route in TAL could explain the coupling between Mg 2+ and Ca 2+ excretion’ ( 157 ) (see below).…”
Section: Urinary Mg2+ Excretionmentioning
confidence: 99%